(untitled) (Al-Academy, 2025)
The topic of aesthetics of functional appropriation in interior design has occupied an important and wide area of attention of interior design theorists, critics, and practitioners. Accordingly, the research focused, within its general problem, on studying the topic of aesthetics of functional appropriation in the design of contemporary interior spaces, which led this study in revealing many variables and transformations over time. After embodying contemporary ideas in the design of these spaces by showing the formal design with new methods and techniques, whether in the design of visual elements or in the style of furnishing those spaces, in order to establish new sensory connections, deliberately showing those designs that possess a shifting form, psychological attraction, and suitability for the user to spend long hours inside. These are the spaces in which the conditions for comfort and adaptation must be met without the user being repulsed by them. The importance of the research was explained in directing interest in studying the aesthetics of functional citation and its representations in the design of contemporary interior spaces represented by contemporary private hospitals. The aim of the research is to reveal the aesthetic variables of functional citation in the design of interior spaces. Contemporary, setting design foundations that include functional quotation in the design of the interior spaces of the waiting hall of private hospitals in Baghdad, and the vocabulary of scientific research was crystallized in the formation of its detailed theoretical framework for these vocabulary, which are: aesthetics, quotation, functional quotation, and contemporary interior spaces, as this framework constituted an achievement of the first stage. The scientific research method in solving its problem. The second stage is applying the theoretical framework in the research procedures on which the researcher relied. The research sample was taken from the most prominent hospitals that include the aesthetics of functional quotation in their structural composition of the interior spaces. The application of research procedures also required specifying theoretical indicators for the study to be applied, the objectives of scientific research, the method of collecting information in the practical study, and analyzing its results.